CURRENT UNDERSTANDING OF TYPE I DIABETES MELLITUS - Kudratova Z. E.; Nabieva F.S.; Sa'dullaev S.E. (Journal of new century innovations, 2023)
Abstract. Diabetes mellitus is an extremely widespread chronic disease, ranking third among the leading causes of death: after cardiovascular and oncological diseases.